2012
DOI: 10.4067/s0718-16202012000100006
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant properties and color of Hibiscus sabdariffa extracts

Abstract: 100 g -1 of calyces. The total monomeric anthocyanin content (209±21 mg . 100 g -1 ) was similar to that obtained using the HPLC technique (215±31 mg . 100 g -1 ) when extracting the calyces with the 50:50% (v/v) ethanol:water solution. The deepest red-purple (Hue = 62.50±0.34) colored solution was observed when extracting the calyces with ethanol. The antioxidant and color properties of Roselle calyces make the extracts ideal for use in foods as a natural extract, concentrate, or powder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 29 publications
(27 reference statements)
2
20
1
6
Order By: Relevance
“…In general, these levels are higher than those found in the literature (Table 1). Salazar-González et al (2012) obtained up to 2.08 mg CT/g P (1.33 mg C1/g and 0.75 mg C2/g) when performing a 120-min extraction with ethanol:water mixtures (50:50, v/v) at a S/L of 100 g/L and room temperature. Up to 7.92 mg CT/g R (4.11 mg C1/g and 3.81 mg C2/g) were achieved by Sindi et al (2014) with aqueous extractions of 10 min at 100°C.…”
Section: Experimental Data For Rsm Optimizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, these levels are higher than those found in the literature (Table 1). Salazar-González et al (2012) obtained up to 2.08 mg CT/g P (1.33 mg C1/g and 0.75 mg C2/g) when performing a 120-min extraction with ethanol:water mixtures (50:50, v/v) at a S/L of 100 g/L and room temperature. Up to 7.92 mg CT/g R (4.11 mg C1/g and 3.81 mg C2/g) were achieved by Sindi et al (2014) with aqueous extractions of 10 min at 100°C.…”
Section: Experimental Data For Rsm Optimizationmentioning
confidence: 99%
“…Most of the phytochemical studies on the H. sabdariffa constituents have been directed towards the characterization of pigments, namely anthocyanins (Ali et al, 2005;Beye, Hiligsmann, Tounkara, & Thonart, 2017;Jabeur et al, 2017). Delphinidin-3-glucoside, cyanidin-3-glucoside, and in particular delphinidin-3-sambubioside (hibiscin) and cyanidin-3-sambubioside (gossypicyanin) have been identified in calyx extracts (Alarcón-Alonso et al, 2012;Beye et al, 2017;Salazar-González, Vergara-Balderas, Ortega-Regules, & Guerrero-Beltrán, 2012). These anthocyanins are responsible for the characteristic red colour of the H. sabdariffa calyces and can be recovered for subsequent use as colorants in different industrial sectors.…”
Section: Introductionmentioning
confidence: 99%
“…Mungole (2011) reported an EC 50 of 0.13 mg/mL and 88.03 % inhibition in alcoholic Roselle extracts. Mohd-Esa et al (2010) conducted a study for determining phenolics content of different parts of Roselle plant (seed, calyces, leaf, and stem); they reported a content of total phenols (by Folin-Ciocalteu method) of 1.85±0.1 mg Gallic acid/g of calyces (30.8±1.4 % of inhibition) in aqueous extracts, and 2.91±0.07 mg Gallic acid/g of calyces (87.9± González et al (2012) reported 209±21 mg anthocyanins/ 100 g (differential pH method), 2,415 ± 96 mg Gallic acid/100 g (Folin-Ciocalteu method), and 8,035±220 μM Trolox/100 g (about 2,011.1 mg Trolox/100 g) (ABTS (2,2'-azinobis (3-ethylbenzothiazoline-6-sulfonic acid) method) of Roselle using a 50:50 ethanol:water ratio. Cid-Ortega and Guerrero-Beltrán (2014) reported a content of anthocyanins (differential pH method) and total phenols (Folin-Ciocalteu method) in Roselle calyces extracts from powder (average particle size of 0.55±0.016 mm) of 451.4±28.1 mg/100 g and 2,016.2±159.8 mg Gallic acid/100 g, respectively, carrying out the extraction with 50 % ethanol at 50°C for 30 min.…”
Section: Bioactive Compoundsmentioning
confidence: 99%
“…The extracts were obtained by stirring; they mixed one gram of Roselle in one L of solvent for 2 hours at room temperature. Salazar-González et al (2012), who used the same Roselle variety, as the one used in this study, reported an anthocyanins concentration of 209 ± 21 mg/100 g of Roselle and a total phenolics content of 2415 ± 96 mg/100 g of Roselle in 50:50 % (v/v) ethanol:water extracts. Differences in results from this work and other studies are mainly due to the variety of Roselle, as well as sample:solvent ratio, extracting method, and type of solvent.…”
Section: Total Anthocyanins Content (Tac)mentioning
confidence: 99%